Surrealism & its Affinities : The Mary Reynolds Collection. A bibliography compiled by Hugh Edwards. - Edwards, Hugh (Chicago : The Art Institute of Chicago, 1973)
Breton, André ; Dali, Salvador ; Domela, César ; Eluard, Paul ; Ernst, Max ; Dubuffet, Jean ; Duchamp, Marcel ; etc.
Engels
boek